MINDFULNESS ART FROM NATURAL COLORS - Premnirundon, Jackthanarchon; Pholprasert, Apichart; Boonyananta, Soamshine (Journal of Buddhist Anthropology, 2024)
Background and Objectives: In recent years, the use of natural colors has become one of the popular options for artists and art educators. Working with nature helped adjust the mind to be calm and concentrated. Pigments extracted from nature were not only safe for the body and the environment but also sustainable materials readily available from local areas. Thus, the objectives of this research article were to study and analyze processes for extracting natural colors for use in art creation and art activities and to present guidelines for organizing mindfulness art activities using colors extracted from natural materials. Methodology: This research was a systematic review. Data were analyzed from 24 selected research articles, which were categorized into four main issues: 1) The extraction of natural colors for art creation; 2) The use of natural colors in art activities; 3) Art for mindfulness; and 4) Natural colors and mindfulness. The tools used in this research included: 1) A research quality assessment form related to the topic studied and criteria for evaluating research quality; and 2) A data recording form consisting of general information about the research, such as the name of the author, year of publication, sample group, research methods, and research results. Main Results: 1) The research findings indicated that art activities using natural colors enhanced mindfulness and 2) A guideline for organizing Mindfulness Art Activities from Natural Colors (MAANC Model) was proposed, which consisted of Mindfulness: Adjusting the mind to be calm by engaging with nature and natural materials, allowing the mind to become meditative; Research: Extracting and experimenting with natural materials to find the desired colors for use in art; Skill: Utilizing artistic skills to create art from natural colors extracted independently. Involvement to Buddhadhamma: The results of this research were categorized as Applied Buddhism, representing the integration of Buddhism with modern or contemporary knowledge. This work fell within the realm of Buddhism and the development of wisdom and morality. The purpose was to present guidelines for organizing mindfulness art activities using natural colors. These activities combined art creation with meditation, using nature as a medium to achieve concentration and peace. Physiological responses to being in a natural environment, such as decreased heart rate, were observed, contributing to mental rejuvenation, improved concentration, and a deeper sense of connection. The processes involved in making art, from extracting colors to experimenting with and applying them, aligned with the Dhamma principles of the Four Iddhipada (Four Paths of Accomplishment): 1) Chanda (Passion) The satisfaction of exploring and experimenting with creating art from natural materials; 2) Viriya (Diligence) The perseverance to work on art with dedication until its completion; 3) Citta (Mindfulness or Consciousness) The focused intention to research, experiment, and extract colors for the artwork; and 4) Vimamsa (Investigation) The effort to evaluate, plan, examine, and improve the artwork for optimal results. Conclusions: Humans were inherently connected to nature. Working with natural materials brought them closer to their origin, evoking feelings of comfort and belonging. This connection fostered Chanda (Passion), which supported other creation processes until completion. Working with natural colors demonstrated a tendency to calm the mind. Furthermore, art activities using natural colors positively influenced meditation, promoting mindfulness and mental clarity.